2019
DOI: 10.24109/2176-6681.rbep.94i237.370
|View full text |Cite
|
Sign up to set email alerts
|

Repetência escolar nos anos iniciais do ensino fundamental: evidências a partir dos dados da Prova Brasil 2009

Abstract: Apresenta os resultados de um estudo exploratório sobre a repetência escolar de alunos dos anos iniciais do ensino fundamental. Usando os dados dos estudantes do 5º ano avaliados na Prova Brasil 2009, em Matemática, programou-se um modelo de regressão logística (modelo de risco à eprovação) para investigar quais características dos alunos e de suas famílias estão associadas à repetência. Verificou-se no estudo que os meninos são mais propensos à repetição em Matemática do que as meninas e que cursar a pré-esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
4
0
6
Order By: Relevance
“…However, adolescents above 16 years fall outside the typical age for ninth grade, thus these students possibly have a history of grade retention and are more likely to present other characteristics of social vulnerability. Grade retention in Brazil is more frequent among boys, blacks, lower social classes, students whose parents have lower levels of education and among those whose parents do not attend school meetings nor support the accomplishment of tasks [51]. Also noteworthy is the higher prevalence of co-occurrence of risk factors in females.…”
Section: Discussionmentioning
confidence: 99%
“…However, adolescents above 16 years fall outside the typical age for ninth grade, thus these students possibly have a history of grade retention and are more likely to present other characteristics of social vulnerability. Grade retention in Brazil is more frequent among boys, blacks, lower social classes, students whose parents have lower levels of education and among those whose parents do not attend school meetings nor support the accomplishment of tasks [51]. Also noteworthy is the higher prevalence of co-occurrence of risk factors in females.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is also defended in a study carried out by Ortigão and Aguiar [22] when they found that in the educational literature, there has been an improvement in the performance of women when compared with men. These authors, indicate that this situation is related to a better adaptation of the girls to the school, given the primary and familiar socialization that favors a more orderly and obedient behavior.…”
Section: Characteristics Of the Families Of Students In The Schools Smentioning
confidence: 90%
“…As it turns out, students whose parents have a low level of schooling makes it difficult for the children to have a satisfactory situation in school, since within the family there are no people able to support them in their school activities or to have them as models or references. The existence of a family context characterized by a study support environment allows the students to have better school performance [22].…”
Section: Final Considerationsmentioning
confidence: 99%
“…Inúmeros estudos apontam que, quanto maior o nível de escolaridade dos pais, melhor o desempenho de seus filhos (JESUS;LAROS, 2004;AGUIAR, 2013;CARVALHO, 2007). Notoriamente, as consequências extrapolam a sala de aula e o êxito acadêmico, acarretando, futuramente, sucesso profissional.…”
Section: Aspectos Críticosunclassified